Impact of the period of the day on all-cause mortality and major cardiovascular complications after arterial vascular surgeries - Thiago Artioli; Danielle Menosi Gualandro; Francisco Akira Malta Cardozo; María Carmen Escalante Rojas; Daniela Calderaro; Pai Ching Yu; Ivan Benaduce Casella; Nelson de Luccia; Bruno Caramelli (PLoS ONE, 2023)
Background Conflicting results are reported about daytime variation on mortality and cardiac outcomes after non-cardiac surgeries. In this cohort study, we evaluate whether the period of the day in which surgeries are performed may influence all-cause mortality and cardiovascular outcomes in patients undergoing non-cardiac arterial vascular procedures. Methods 1,267 patients who underwent non-cardiac arterial vascular surgeries between 2012 and 2018 were prospectively included in our cohort and categorized into two groups: morning (7 a.m. to 12 a.m., 79%) and afternoon/night (12:01 p.m. to 6:59 a.m. in the next day, 21%) surgeries. Primary endpoint was all-cause mortality within 30 days and one year. Secondary endpoints were the incidence of perioperative myocardial injury/infarction (PMI), and the incidence of major adverse cardiac events (MACE, including acute myocardial infarction, acute heart failure, arrhythmias, cardiovascular death) at hospital discharge. Results After adjusting for confounders in the multivariable Cox proportional regression, all-cause mortality rates at 30 days and one year were higher among those who underwent surgery in the afternoon/night (aHR 1.6 [95%CI 1.1–2.3], P = 0.015 and aHR 1.7 [95%CI 1.3–2.2], P < 0.001, respectively). Afternoon/night patients had higher incidence of PMI (aHR 1.4 [95%CI 1.1–1.7], P < 0.001). There was no significant difference in the incidence of MACE (aHR 1.3 [95%CI 0.9–1.7], P = 0.074). Conclusions In patients undergoing arterial vascular surgery, being operated in the afternoon/night was independently associated with increased all-cause mortality rates and incidence of perioperative myocardial injury/infarction.